THE ANALYSIS OF USING ARTICULATE STORYLINE IN THE NARRATIVE TEXT OF EIGHTH GRADE AT MTS ALHIDAYAH ISLAMIYAH SOSIAL, HATONDUHAN IN 2024/2025 ACADEMIC YEAR - Mungkap Mangapul Siahaan; Sarah Aufah Athiya; Yanti Kristina Sinaga; Irene Adryani Nababan (RADJA PUBLIKA, 2025)
This research aims to analyze students’ reading comprehension ability and the difficulties they encounter in learning English. According to Sugiyono (2011: 55), a qualitative research method is a research method based on the philosophy of post-positivism, used to research natural object conditions (as opposed to experiments) where the researcher is the key instrument, data source sampling is carried out purposively and snowball, data collection techniques with triangulation (combination), data analysis is inductive or qualitative, and qualitative research results emphasize meaning more than generalization. The study employed a qualitative descriptive method involving 30 eighth-grade students as respondents. Data were collected through observation and interviews to obtain a detailed understanding of students’ reading performance. The results indicate that students’ reading comprehension ability is divided into three levels: low, middle, and high. Among the participants, 15 students (50%) are categorized as low, 8 students (26.7%) as middle, and 7 students (23.3%) as high. These findings suggest that the majority of students still face difficulties in understanding the content and meaning of English narrative texts. The study highlights the importance of using effective learning media and teaching strategies to enhance students’ English reading comprehension.